Discrete-Continuous Models In Nonlinear Dynamic Investigations of Selected Physical Systems - Pielorz, A. (Engineering Transactions, 1999)
The paper deals with dynamic investigations of nonlinear discrete-continuous models in which elastic elements are deformed torsionally, longitudinally or transversally, and the classical wave equation can be used for the description of their motion. The investigations focus on nonlinear vibrations of the discrete-continuous models with a local nonlinearity described by the polynomial of a third degree. The detailed analysis for a simple nonlinear discrete-continuous system is done. It is shown that amplitude jumps in the case of a hard characteristic and the escape phenomenon in the case of a soft characteristic can occur.